A chromosome-level genome assembly of Electrophorus voltai, a species of electric eel - Yuanyuan Wang; Yi Liu; Yexin Yang; Chao Bian; Chao Liu; Yang Zhang; Xidong Mu (Scientific Data)
Abstract Electrophorus voltai, a South American electric eel, is renowned as the most powerful bioelectricity generator, capable of producing electric discharges reaching 860 volts. This remarkable ability positions it as an invaluable model for investigating the genetic, physiological, and developmental mechanisms driving electrogenesis in vertebrates. Here, we report a chromosome-level genome assembly of E. voltai, constructed using PacBio HiFi long reads and Hi-C scaffolding. The final assembly spans 666.91 Mb, with a contig N50 of 1.54 Mb and a scaffold N50 of 28.42 Mb, anchored onto 26 chromosomes. Genome annotation revealed 23,221 protein-coding genes, of which 22,306 genes were functionally annotated. Repetitive sequences account for 298.83 Mb of the genome, dominated by transposable elements. Additionally, we identified 225 miRNAs, 5,409 tRNAs, 288 rRNAs, and 535 snRNAs. This genome provides a foundational resource for comparative genomic studies of electric fish and facilitates investigations into the evolution of electrogenesis, electrocyte development, and bioelectric signal regulation in vertebrates.